Development and Characterization of Fermented Fat Spread from Cow Milk and Coconut Milk Creams - Jayasooriya DGSC; Dias PGI (Talenta Publisher, 2026)
Background: Dairy alternatives that reduce unhealthy animal fat are an emerging food trend. Although plant-based fermented fat spreads are available globally, they remain limited in Sri Lanka. Objective: This study aimed to develop a fermented fat spread using cow and coconut milk creams. Methods: Five formulations were prepared: NFCC, NFCOC, FCC, FCOC, and a 1:1 fermented blend (FMC). Fermentation used mixed cultures of Lactobacillus spp., Streptococcus spp., and Bifidobacterium lactis. Analyses included yield, churning efficiency, composition, melting point, texture, sensory properties, and shelf stability. Results: FCOC showed significantly higher (p<0.05) churning efficiency, fat content, and unsaturated fatty acids, with a lower melting point (27.33 ± 0.50 °C). Blending fermented creams improved the melting point (30.67 ± 0.57 °C) and texture stability at room temperature. Coconut cream enhanced cohesiveness and spreadability. NFCC had the highest overall sensory acceptability, while FMC scored highest for appearance. FCOC exhibited superior shelf stability with lower peroxide values and microbial counts. Conclusion: The blended fermented spread offers a promising method for improving healthy fat while enhancing the texture stability and cost-effectiveness of the process. This method may avoid chemical hydrogenation-induced trans-fat formation in plant-based fat spreads.